INTERRELATIONSHIP OF INDEXES OF THYROID STATUS, THE STATE OF LIPID PEROXIDATION AND ANTIRADICAL DEFENCE IN ANIMALS IN CONDITIONS OF HYPOTHYROID DYSFUNCTION - Тучак, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The interrelationship of indexes of thyroid status, the state of lipid peroxidation and antiradical defense in animals in conditions of hypothyroid dysfunction has been studied. It has been revealed that the level of thyroxin in blood serum with high degree of probability influences on the level of diene conjugates in thyroid gland (r=-0,94) and malone aldegide in diencephalon (r=-0,84) and thyroid gland (r=0,86).